CLUBES DE LEITURA: UM ESTUDO DAS POTENCIALIDADES FORMATIVAS DO CLUBE DE LEITURA LIV/UFOPA NA CIDADE DE SANTARÉM- PARÁ - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
Reading clubs have been seen as important ways of promoting reading in several countries around the world. Its modes of realization reveal several ways of seeing and thinking about reading in the social environment, among which reading stands out as entertainment or as a utilitarian practice and, in some cases, reading as an instrument for human formation. Within this perspective, this paper aims to present how the activities in a reading club space are reflected in the training process of its participants. This investigation was carried out within the scope of the Ler, Interagir e Viver-LIV-Ufopa reading club, a space in which, in addition to being a researcher, I was also a participant, so that I could monitor the development of actions and the formation of the group. As this theme is still new in Brazil, this study required important base for reflection, which led us to conduct a conceptual survey, through which we present important reflections on reading clubs, reading and training clubs. To conduct our research, we considered both historical-cultural and Critical Theory elements. Thus, starting from the formative perspective as defended by Adorno (1995), we implemented and monitored the activities of the LIV reading club over a year and a half, which, within the actions, points out the difficulties faced by the group, as training potentials, as well as to identify important moments related to the development of the goup, especially of the coordinating team.
Keywords: Formação; Leitura Literatura; Clube de Leitura; Conhecimento e Formação na Educação Escolar; Educação na Amazônia